(untitled) (Forum Penelitian Agro Ekonomi, 2016)
This paper discusses an idea on future livestock and how to bring the idea into reality. The sources of the paper are taken from various livestock research results along with the overview of relevant economics theories. Based on these sources, it is concluded that the future livestock could be designed and could also be materialized. However, the government should not recklessly encourage the community to move forward and directly allocate the existing resources. Instead, the government should allow the community to design future livestock by themselves through free market mechanims. On the other hand, government policies should be directed to focus on servicess and draw positive responses to basic livestock problems to enhance market mechanisms. Old paradigm saying that livestock business is a employment opportunity for the community should no longer used and should be changed to a new paradigm saying that livestock business has a function to encourage agroindustry development for a more open and widen employment and business opportunities. The implication of this idea is that the government is suggested to design a national livestock development roadmap with its details in livestock development region of each regencies. This roadmap will be very helpful in program development preparation which also encourage the autonomous inter-regency cooperation.